2009
DOI: 10.1063/1.3110702
|View full text |Cite
|
Sign up to set email alerts
|

Healing of oxygen vacancies on reduced surfaces of gold-doped ceria

Abstract: Access to the full text of the published version may require a subscription. As an oxidation-reduction catalyst, ceria can catalyze molecular oxidation and reduction. There has been a focus on understanding and enhancing the vacancy formation process to improve the oxidative power of ceria. However, it is important to also address healing of the surface vacancy. To investigate healing of oxygen vacancies in ceria, we study the interaction of atomic and molecular oxygen and NO 2 with oxygen vacancies on gold-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 40 publications
6
49
0
Order By: Relevance
“…Some authors have established that oxygen vacancies can act as preferential structural sites for the selective deposition of gold, which would increase the dispersion of the noble metal [45,[48][49][50][51]. The interaction of the oxygen vacancies in CeO 2 with other metals such as Rh, Ir, Pd and Pt has been also observed and associated to a metal-support strong interaction model, named metal nesting, by the filling of the oxygen vacancies with the metallic atoms [52].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have established that oxygen vacancies can act as preferential structural sites for the selective deposition of gold, which would increase the dispersion of the noble metal [45,[48][49][50][51]. The interaction of the oxygen vacancies in CeO 2 with other metals such as Rh, Ir, Pd and Pt has been also observed and associated to a metal-support strong interaction model, named metal nesting, by the filling of the oxygen vacancies with the metallic atoms [52].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to the experimental studies, some of the dopants that have been thoroughly examined are Au [20,22,23], Cu [3,24,26], Pd [3,21,25,[27][28][29], and Zr [1,16,34,35], with concentration on surface reducibility as well as CO, CH 4 , H 2 , or H 2 O interactions with the surface. Using Au as a dopant in the CeO 2 lattice for CO oxidation allows the surface oxygen atoms to become reactive, but not too reactive that the oxygen vacancies will not heal.…”
Section: Introductionmentioning
confidence: 99%
“…The dopant metal may either alter the reducibility of the ceria metal atoms or the dopant can become the reduction center [14][15][16][17]. Several experimental [8][9][10][11][12][13]18,19] and theoretical studies [1][2][3][20][21][22][23][24][25][26][27][28][29] have examined how one or two transition metal dopants can affect the activity of the ceria surface; however, an electronic level explanation remains incomplete. For example, density functional theory (DFT) studies have demonstrated that Pd becomes the reduction center for O-vacancy formation or methane conversion when doped into CeO 2 [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work indicates that healing of the vacancy with gas phase oxygen 11,17 or with NO 2 18,19 is favourable so that the determining step is the initial removal of the oxygen vacancy. The formation energy of oxygen vacancy in bulk CeO 2 is ca.4.5 eV 20,22 .…”
Section: Introductionmentioning
confidence: 99%